Molecular Detection and Subtyping of Blastocystis in Korean Pigs - Paik, Seunghyun; Jung, Byeong Yeal; Lee, Haeseung; Hwang, Mi-Hye; Han, Jee Eun; Rhee, Man Hee; Kim, Tae-Hwan; Kwon, Oh-Deog; Kwak, Dongmi (Korean journal of parasitology, 2019)
Blastocystis is one of the most commonly detected genera of protozoan parasites in the human intestines as well as the intestines of many other species such as pigs in several geographical regions worldwide. However, no studies have examined Blastocystis in pigs in Korea. In this study, PCR and nucleotide sequencing were performed to evaluate the genetic diversity and zoonotic potential of Blastocystis using pig fecal samples. We obtained 646 stool samples from groups of piglets, weaners, growers, finishers, and sows in Korea. A total of 390 Blastocystis-positive samples were identified, and the infection rate was 60.4%. The infection rates were significantly related to age and region. The 4 subtypes (STs) of Blastocystis confirmed by phylogenetic analysis were ST1, ST2, ST3, and ST5, indicating the high genetic diversity of Blastocystis in Korean pigs. ST5 was highly distributed in Korean pigs among detected STs in this study. Some sequences were closely related to those of Blastocystis isolated from humans. This is the first study of Blastocystis in pigs in Korea. Based on the results, Blastocystis is prevalent in Korean pigs. Although a small number of samples were obtained in some areas, the clinical development of Blastocystis infection in pigs and potential for human transmission should be further examined.